The Effect of Financial Performance on Dividend Policy Study on Food and Beverage Companies Listed on Indonesia Stock Exchange 2010-2013 - Sianipar, Dian Natalia; Kuswardono, Anon (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This study aims to determine the relationship between financial performance which measured by return on equity (ROE), return on assets (ROA), and economic value added (EVA) to dividend policy which measured by dividend payout ratio (DPR). The population of this research is all food and beverage companies listed in Indonesia Stock Exchange from 2010-2013 which consisted of 16 companies. The samples are chosen by the use of purposive sampling method and come up with seven companies to be studied. To analyze the data and to perform hypotheses tests using simple linear regression and multiple linear regressions. The results of the hypotheses tests concludes that two variables, return on equity and return on assets have significant influence to dividend payout ratio while economic value added has no significant influence to payout ratio. It was found also that return on equity, return on assets, and economic value added simultaneously have significant influence to payout ratio.